Anti-Friedel–Crafts-Type Substitution To Form Biaryl Linkages - Gulyas-Fekete, Gergely; Boluda, Carlos J.; Westermann, Bernhard; Wessjohann, Ludger A. (Synthesis, 2013)
The ipso-substitution of one (or two) hydroxy groups of phloroglucinol with arene nucleophiles (e.g., o-xylene, tetralin, biphenyl) can be achieved easily under Friedel–Crafts-type conditions with or without the use of organic solvents affording a variety of 3,5-dihydroxybiphenyls (57–89% yields). The new method has significant practical advantages compared to classical biaryl-coupling routes.
Keywords: biaryls; dendrimers; arylations; umpolung; Friedel–Crafts